A Framework For Processing Keyword-Based Queries In Relational Databases For Exact Record - Dwivedi, Anshu Kumar; Sharma, Ashok Kumar (International Journal of Computer Sciences and Engineering, 2014)
Database management system a very strong concept used that is relational database management system. A relational database is often operated by means of a structured query language (SQL). When composing SQL-queries one must have an understanding of the SQL syntax to be able to produce a query the database can execute. Additionally, one must be familiar with the attributes and relations in the database to be able to retrieve the data desired. When one wants to search the available data stored in the relational database, these requirements can be discouraging. In this case keyword-based search functionality could improve the accessibility of the data. The main advantage of RDBMS is its fast accurate, standard way to store data on permanent basis extraction of data is done using SQL its secure (different level of security) data can be managed in proper manner. ACID properties are features if RDBMS stands for Accuracy Consistency Isolation Durability.